2022
DOI: 10.5937/straman2200013m
|View full text |Cite
|
Sign up to set email alerts
|

Exploring direct and non-linear effects of entrepreneurial orientation and its dimensions on firm performance in a small, open, transitional economy

Abstract: Background: The relationship between entrepreneurial orientation (EO) and small firm performance has been extensively researched over the last couple of decades. However, the scientific community still does not have a unanimous view regarding non-linear relationships between EO and performance, especially when adding separate EO dimensions. Purpose: This paper explores the non-linear relationship between EO, observed as a unidimensional and multidimensional construct, and small business performance within a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
1
10
0
1
Order By: Relevance
“…Jednak społeczność naukowa nadal nie 36 ma jednomyślnego poglądu na temat nieliniowych związków pomiędzy OP a wynikami firmy, szczególnie w przypadku dodania odrębnych wymiarów OP. Milovanović (2022) wykazał, że OP ma bezpośredni i nieliniowy związek -w kształcie odwróconej litery U -z wynikami małych firm.…”
Section: Wpływ Orientacji Przedsiębiorczej Na Wzrost Przedsiębiorstwaunclassified
“…Jednak społeczność naukowa nadal nie 36 ma jednomyślnego poglądu na temat nieliniowych związków pomiędzy OP a wynikami firmy, szczególnie w przypadku dodania odrębnych wymiarów OP. Milovanović (2022) wykazał, że OP ma bezpośredni i nieliniowy związek -w kształcie odwróconej litery U -z wynikami małych firm.…”
Section: Wpływ Orientacji Przedsiębiorczej Na Wzrost Przedsiębiorstwaunclassified
“…EO and its dimensions enhance the development of a company and its chance to survive during rapid changes in market conditions – especially in hostile and unfavorable environments (Covin and Slevin, 1989; Zahra and Covin, 1995; Lumpkin and Dess, 2001; Rosenbusch et al. , 2013; Teece, 2014; Morić-Milovanović, 2022; Kusa et al. , 2022; Suder, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…EO has been recognized for more than a dozen years as a key element of entrepreneurial activity that is related to (and positively affects) firm performance (Naldi et al, 2007;Runyan et al, 2008;Baker and Sinkula, 2009;Rauch et al, 2009;Kraus et al, 2012;Wales et al, 2013;Shirokova et al, 2016;Brownhilder, 2016;Al-Mamary et al, 2020;Kusa et al, 2021) and competitive advantage (Semrau et al, 2016). EO and its dimensions enhance the development of a company and its chance to survive during rapid changes in market conditionsespecially in hostile and unfavorable environments (Covin and Slevin, 1989;Zahra and Covin, 1995;Lumpkin and Dess, 2001;Rosenbusch et al, 2013;Teece, 2014;Mori c-Milovanovi c, 2022;Kusa et al, 2022;Suder, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable amount of research focused on the effects EO has on firm performance (Morić-Milovanović 2022; Putnin , š and Sauka 2020; Gupta and Wales 2017;Wales et al 2015). Generally, a positive relationship has been established (Morić-Milovanović 2022;Putnin , š and Sauka 2020;Andersén 2010;Rauch et al 2009); however, many authors question the linearity of such a connection (Lomberg et al 2017;Gupta and Batra 2016;Kreiser et al 2013;Wales et al 2013;Tang and Tang 2012). Some studies found a linear relationship in one group of companies and presence of nonlinear relationship in others (Kreiser et al 2013;Tang and Tang 2012;Su et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al's (2008) findings indicate that the EO-performance relationship might be moderated by institutional framework. Thus, many researchers (Morić-Milovanović 2022;Morić-Milovanović et al 2021;Šlogar 2021;Veselinović et al 2021;Petrović et al 2015;Morić-Milovanović 2012) from southeast European (SEE) countries have responded to Tang et al's (2008) call for further research on the EO-firm performance relationship, specifically in the context of transitional economies. Transitional economies are interesting for investigating the effects of EO on firm performance since they are characterized by volatility of the business and institutional environments, and the importance social capital has on political ties and government control of resources (Luu and Ngo 2019).…”
Section: Introductionmentioning
confidence: 99%